INTASC AND MODALITY ON SPEAKING: HOW EFFECTIVE? - Muliani, Muliani; Sumarsono, Dedi (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2018)
The concern of this current research is based on the consideration that Speaking is urgently needed in acquiring the target language such as English. Then, the problem is mostly dealing with the ability to speak regarding the culture of the target language aiming at getting the approximation to the language being acquired. InTASC standard cores are offered to assist the students of SMAN 1 Kopang in which the standards were implemented that it is expected they are able to communicate in English. Eventually, it was found that InTASC standard cores are effective to assist the students’ speaking in which the standards meet the whole indicators of Speaking.